2016
DOI: 10.4314/njp.v43i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rotavirus among children under five years of age with diarrhea in Kaduna State, Nigeria

Abstract: Rotavirus (RV) is a major etiological agent of acute infantile gastroenteritis and is associated with 20%-25% of diarrhea cases in infants. Nigeria continues to be among the first five countries with greatest number of RV disease associated deaths per year. The objective was to determine some demographic factors that might be associated with rotavirus diarrhea among children in Kaduna State. From September 2013-August 2014, 401 diarrheic stool samples were collected from children under 5 years of age in Kaduna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
10
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 21 publications
11
10
3
Order By: Relevance
“…Numerous studies have shown the important role of rotaviruses as a cause of diarrhea in children in developed and developing countries, most of which have occurred in children under 5 years of age [ 16 , 17 ]. This prevalence is similar to that in [ 18 , 19 , 20 , 21 ], Kenya [ 22 ], and Jordan [ 23 ] in children of the same age. It is higher than that found in Gabon [ 24 ] and Angola [ 25 ].…”
Section: Discussionsupporting
confidence: 83%
“…Numerous studies have shown the important role of rotaviruses as a cause of diarrhea in children in developed and developing countries, most of which have occurred in children under 5 years of age [ 16 , 17 ]. This prevalence is similar to that in [ 18 , 19 , 20 , 21 ], Kenya [ 22 ], and Jordan [ 23 ] in children of the same age. It is higher than that found in Gabon [ 24 ] and Angola [ 25 ].…”
Section: Discussionsupporting
confidence: 83%
“…A study conducted among children in Ibadan in 2016 reported a prevalence of 18.5% [ 38 ]. The most recent report from Northern Nigeria recorded a prevalence rate of 32.2% of rotavirus induced gastroenteritis among children in Kaduna [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infected children may also have a cough and runny nose. 8,9,10,11,12,13 Generally, reinfections are common in Rotavirus disease. 14 Immunity develops with each infection, so subsequent infections are less severe; adults are rarely affected.…”
Section: Introductionmentioning
confidence: 99%